PELAKSANAAN UPACARA ADAT PERKAWINAN MASYARAKAT MELAYU DI DESA KAPUAS RAYA KECAMATAN BUNUT HILIR KABUPATEN KAPUAS HULU - NIM. A1012191004, DIMAS ANGGRA SAPUTRA (Jurnal Fatwa Hukum, 2022)
Abstrac The implementation of the Malay Community Traditional Marriage Ceremony in Kapuas Raya Village, Bunut Hilir District, Kapuas Hulu Regency is a manifestation of the Malay Indigenous People and their belief in their ancestors and ancestors. In the social life of the Malay Indigenous People in Kapuas Raya Village, they adhere to the provisions of customary law as a guideline for attitude and behavior that covers the whole of life, meaning that it includes marriage. Marriage has an important meaning for the Malay Indigenous People in Kapuas Raya Village, not only to get offspring but also as an important thing to do. The procedure for carrying out the traditional Malay marriage ceremony in Kapuas Raya Village is divided into two, namely before the Marriage Agreement and after the Marriage Agreement which includes: Mission (Introduction Period), Bepintak (Asking), Besurung (Engaged), Mutual Cooperation, Berzanzi ( Reading of the Holy Qur'an verses Bestep (Dance), Beaci (Besolek), after the Marriage Agreement includes: Marriage Agreement (Ijab Qabul), Fresh Flour (Congratulations Prayer), Safe Bathing (Bathing for Safety), and Amik Main (Visiting Husband's House). In its implementation, it underwent several shifts from its original form, which underwent a shift, namely the implementation of Bestep or Dancing and Besurung or Engagement.The formulation of the problem in this research is "Is the Traditional Marriage Ceremony of the Malay Community in Kapuas Raya Village, Bunut Hilir District, Kapuas Hulu Regency Has Been Implemented Accordingly?" to reveal what factors caused the shift in the stages of the traditional Malay wedding ceremony, to reveal the consequences that arise when the traditional wedding ceremony is not fully carried out by the Malay Indigenous People in Kapuas Raya Village, and finally to reveal the efforts of the traditional leader (penggawa) in preserving the customary the traditional way as a whole. The research method used is the Empirical Research Method with descriptive research characteristics.The results of the study obtained that the Malay Community's Traditional Marriage Ceremony in Kapuas Raya Village, Bunut Hilir District, Kapuas Hulu District that experienced a shift was the implementation of the traditional ceremony before the marriage contract or Kabul consent, namely a series of bestep or dancing events and a series of besurung or engagement events, the factors that led to the occurrence shift is the development of modern times. The legal consequences that arise in customary law are moral sanctions in the form of ridicule from the community and are considered by the community to not preserve adat. The legal action taken is to obtain data and information as well as an overview of the implementation of the traditional Malay marriage ceremony, reveal what factors cause the shift, then look for the consequences that arise if the traditional marriage ceremony is not carried out fully, and carry out the efforts of the traditional leader in preserving the procedures the traditional way as a whole.Keywords: Traditional Ceremony, Marriage, Malay Society Abstrak Pelaksanan Upacara Adat Perkawinan Masyarakat Melayu Di Desa Kapuas Raya Kecamatan Bunut Hilir Kabupaten Kapuas Hulu merupakan perwujudan dari Masyarakat Adat Melayu dan kepercayaan terhadap para leluhur dan nenek moyang. Dalam kehidupan sosial Masyarakat Adat Melayu di Desa Kapuas Raya ini berpegang teguh pada ketentuan hukum adat sebagai pedoman bersikap dan bertingkah laku yang mencangkup seluruh kehidupan, bermaksud didalamnya perkawinan. Perkawinan mempunyai arti penting bagi Masyarakat Adat Melayu di Desa Kapuas Raya, tidak hanya untuk memperoleh keturunan tetapi juga sebagai hal penting harus dilakukan. Adapun tata cara pelaksanaan upacara adat perkawinan masyarakat adat Melayu di Desa Kapuas Raya dibagi menjadi dua, yaitu sebelum Akad Nikah dan Sesusah Akad Nikah yang meliputi : Misi (Masa Perkenalan), Bepintak (Bertanya), Besurung (Bertunangan), Gotong Royong, Berzanzi (Pembacaan Ayat Suci Al-Qur"™an) Belangkah (Menari), Beaci (Besolek), sesudah Akad Nikah meliputi: Akad Nikah(Ijab Qabul), Tepung Tawar (Doa Selamat), Mandi Selamat (Mandi-Mandi Untuk Keselamatan), Dan Amik Main (Berkunjung Kerumah Suami). Dalam pelaksanaanya mengalami beberapa pergeseran dari bentuk aslinya, yang mengalami pergeseran ialah pelaksanaan Belangkah atau Menari dan Besurung atau Bertunangan.Adapun Rumusan masalah dalam peneltian ini "Apakah Upacara Adat Perkawinan Masyarakat Melayu Di Desa Kapuas Raya Kecamatan Bunut Hilir Kabupaten Kapuas Hulu Telah Dilaksanakan Sesuai Aslinya ?", selanjutnya untuk tujuan penelitian yaitu: untuk mendapatkan data dan informasi serta gambaran tentang pelaksanaan upacara adat perkawinan, Untuk mengungkapkan faktor apa saja yang menyebabkan pergeseran tahapan upacara adat perkawinan Masyarakat Adat Melayu, Untuk mengungkapkan akibat yang timbul apabila upacara adat perkawinan tidak sepenuhnya dilakasanakan oleh Masyarakat Adat Melayu di Desa Kapuas Raya, dan terakhir ialah untuk mengungkapkan upaya ketua adat (penggawa) dalam melestarikan tata cara adat secara utuh. Metode penelitian yang digunakan yaitu Metode Penelitian Empiris dengan sifat penelitian deskriptif.Hasil penelitian yang diperoleh bahwa Upacara Adat Perkawinan Masyarakat Melayu di Desa Kapuas Raya Kecamatan Bunut Hilir Kabupaten Kapuas Hulu yang mengalami pergeseran adalah pelaksanaan upacara adat sebelum akad nikah atau ijab Kabul yaitu rangkaian acara belangkah atau menari dan rangkain acara besurung atau bertunangan, faktor yang menyebabkan terjadinya pergeseran adalah perkembangan zaman yang sudah modern. Akibat hukum yang timbul dalam dalam hukum adat ialah sanksi moral berupa cemoohan dari masyarakat dan dianggap oleh masyarakat tidak melestarikan adat. Upaya Hukum yang dilakukan ialah dengan mendapatkan data dan informasi serta gambaran tentang pelaksanaan upacara adat perkawinan masyarakat adat melayu, mengungkapkan faktor apa saja yang menyebabkan pergeseran,selanjutnya mencari akibat yang timbul apabila upacara adat perkawinan tidak dilaksanakan sepenuhnya, dan melaksanakan upaya ketua adat dalam melestarikan tata cara adat secara utuh.Kata Kunci : Upacara Adat, Perkawinan, Masyarakat Melayu